An empirical study towards efficient learning in artificial neural networks by neuronal diversity - Adamu, Abdullahi Shuaibu (2016)
Artificial Neural Networks (ANN) are biologically inspired algorithms, and it is natural that it continues to inspire research in artificial neural networks. From the recent breakthrough of deep learning to the wake-sleep training routine, all have a common source of drawing inspiration: biology. The transfer functions of artificial neural networks play the important role of forming decision boundaries necessary for learning. However, there has been relatively little research on transfer function optimization compared to other aspects of neural network optimization. In this work, neuronal diversity - a property found in biological neural networks- is explored as a potentially promising method of transfer function optimization.